2021
DOI: 10.3390/met12010044
|View full text |Cite
|
Sign up to set email alerts
|

Capability of Multi-Material Laser-Based Powder Bed Fusion—Development and Analysis of a Prototype Large Bore Engine Component

Abstract: Additive Manufacturing (AM) allows the manufacturing of functionally graded materials (FGM). This includes compositional grading, which enables the allocation of desired materials corresponding to local product requirements. An upcoming AM process for the creation of metal-based FGMs is laser-based powder bed fusion (PBF-LB/M) utilized for multi-material manufacturing (MM). Three-dimensional multi-material approaches for PBF-LB/M are stated to have a manufacturing readiness level (MRL) of 4 to 5. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Schneck et al [ 50 ] proposed a breakthrough of multi-material technology by fabricating a complex, industrial multi-material part as a prototype fabricated by laser-based powder bed fusion. With this work, the authors concluded that a maturation of this type of fabrication to a higher MRL was possible [ 50 ]. Wu et al [ 51 ] performed a literature review and evaluated bioprinting based on the proposed criteria of the MRL.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Schneck et al [ 50 ] proposed a breakthrough of multi-material technology by fabricating a complex, industrial multi-material part as a prototype fabricated by laser-based powder bed fusion. With this work, the authors concluded that a maturation of this type of fabrication to a higher MRL was possible [ 50 ]. Wu et al [ 51 ] performed a literature review and evaluated bioprinting based on the proposed criteria of the MRL.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Regardless of the specific technology in use, much attention in the literature has been paid to embedding functionality through the development of new materials, including alloys and composites, rather than part comprised of multimaterial systems. Generally speaking, multimaterial printing by PBF is still in its infancy, [7] likely because it requires complicated procedures (e.g., the deposition, consolidation, and cleaning of alternating powders' layers [8] ) or extensive hardware customization. [9] Also, multimaterial printing may potentially cause bonding issues at the interface between dissimilar materials, thermal stresses due to the thermodilatometric mismatch, and, in metal-based systems, galvanic corrosion in service, should the materials be bridged by an electrolyte.…”
Section: Powder Bed Fusionmentioning
confidence: 99%
“…Another approach for applying powders in a multi-material process combines a full-surface powder deposition with powder removal by suction 24 . An illustration of this approach is shown in Figure 3 where an AconityONE printer was upgraded with a multi-material mobile module that can be installed and removed.…”
Section: Powder Spreading With Removal By Suctionmentioning
confidence: 99%